Unfractionated Heparin Promotes Osteoclast Formation in Vitro by Inhibiting Osteoprotegerin Activity - Li, Binghan (Int J Mol Sci, 2016)
Heparin has been proven to enhance bone resorption and induce bone loss. Since osteoclasts play a pivotal role in bone resorption, the effect of heparin on osteoclastogenesis needs to be clarified. Since osteocytes are the key modulator during osteoclastogenesis, we evaluated heparin’s effect on osteoclastogenesis in vitro by co-culturing an osteocyte cell line (MLO-Y4) and pre-osteoclasts (RAW264.7). In this co-culture system, heparin enhanced osteoclastogenesis and osteoclastic bone resorption while having no influence on the production of RANKL (receptor activator of NFκB ligand), M-CSF (macrophage colony-stimulating factor), and OPG (osteoprotegerin), which are three main regulatory factors derived from osteocytes. According to previous studies, heparin could bind specifically to OPG and inhibit its activity, so we hypothesized that this might be a possible mechanism of heparin activity. To test this hypothesis, osteoclastogenesis was induced using recombinant RANKL or MLO-Y4 supernatant. We found that heparin has no effect on RANKL-induced osteoclastogenesis (contains no OPG). However, after incubation with OPG, the capacity of MLO-Y4 supernatant for supporting osteoclast formation was increased. This effect disappeared after OPG was neutralized and reappeared after OPG was replenished. These results strongly suggest that heparin promotes osteocyte-modulated osteoclastogenesis in vitro, at least partially, through inhibiting OPG activity.